Indução de calos em anteras de Coffea arabica L. em diferentes meios de cultura - Figueira, Elisângela Rodrigues (2005)
The Coffea arabica shows little progress in anther culture, so it is important to identify the cultivars, the action and the concentration of growth regulators used in culture médium, which is most responsive to androgenesis. The aim of this paper was to apply anther culture technique in different cultivars of Coffea arabica L. to induce callus formation and dihaploids plantlet regeneration The experiments were carried out at plant tissue culture laboratory at Universidade Federal de Uberlândia (UFU). Experiment 1: Flower buds of Mundo Novo and Catuaí Vermelho 99 cultivars were collected, separated in pre-treatments by cold shock (4°C), hot shock (35°C) and environmental temperature, sterilized and the anthers were inoculated in médium MS, supplemented with TDZ (0 001 • 0,01; 0,1 and 1,0 mg.L). After 30 days of in vitro culture, the anthers were subcultivated in médium MS supplemented with 2,4-D (6 mg.L) and TDZ (0 5 mg.L). Experiment 2: Callus of Catuai Vermelho 44 were subcultivated in médium MS supplemented with 2 mg.L of 2,4-D, with presence or not of 5 mc.L de AgNO3 and ASA (0,0; 8,0; 16,0 e 32,0 mg.L). Experiment 3: Flower buds of Mundo Novo and Catuai Vermelho 44 cultivars were collected, sterilized and the anthers were inoculated in médium MS supplemented with 2 mg.L of 2 4-D with presence or not of 5 mg.L de AgNO3 and ASA (0,0; 8,0; 16,0; 32,0 and 64,0 mg.L). After 60 days of in vitro culture, the anthers were subcultivated in médium MS supplemented with 2,4~D (0,0; 1,0 e 2,0 mg.L) and BAP (0,0; 2,0 e 4,0 mg.L). The pre-treatment by cold shock is the most efficient one for the callus induction at in vitro culture of anthers of Coffea arabica L.; the growth regulators 2,4-D and TDZ at the concentrations used are efficient for the callus induction; however they don’t promote the callus regeneration; the silver nitrate (AgNO3) and acetylsalicilic acid (AAS), such as the association of 2,4-D and BAP at the concentrations used aren’t efficient in pro-embryos regeneration in anthers of the cultivars studied; Catuaí Vermelho is the most responsive cultivar at androgenesis when compared with Mundo Novo.